The Effect of Price and Service Quality on Customer Satisfaction PT. Triputro Joyo Mandiri - Suhardoyo Suhardoyo; Nurul Sabrina Fuadah (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to assess the impact of price and service quality on customer satisfaction at PT. Triputro Joyo Mandiri. The population consists of the company’s customers, with a sample of 100 respondents selected using Purposive Sampling. The independent variables include price and service quality, while the dependent variable is customer satisfaction. A quantitative analysis method was employed. The t-test results indicate that price (X1) has a t value of 6.147, exceeding the t table value of 1.985, signifying a significant effect on customer satisfaction (Y). Similarly, service quality (X2) shows a t value of 6.603, indicating significant influence. The F-test yielded an F value of 195.984, greater than 3.09, demonstrating a simultaneous effect of both variables on customer satisfaction. The Adjusted R Square value of 0.802 indicates that 80.2% of customer satisfaction is influenced by price and service quality, with the remaining 18% affected by other factors..